INTERAKSI PESANTREN DENGAN SAINS DAN TEKNOLOGI - Muhammad Abror Rosyidin (Universitas Islam Sultan Agung, 2021)
However, along with the times, pesantren have not only opened religious-based schools, but also public schools that provide general knowledge (natural, social, and language) to their students. Educational formalities in pesantren were also proposed so that pesantren alumni could continue their education to public schools. There are three main problems in this paper by reconstructing the pesantren education system, as follows; (1) the relationship between pesantren and the outside world, (2) the relationship between pesantren and science and technology, and (3) the epistemology of Islamic Science in Pesantren Sains (Trensains). The qualitative descriptive method is the choice in this study. This research is a qualitative field study with case studies. In order to obtain comprehensive data and pay attention to the relationship between the data and the focus and objectives of the research, data collection in this study used three techniques, namely (1) interviews, (2) participant observation: (3) research documentation. Research activities in data analysis include data reduction, data presentation, and drawing conclusions. From this research, it can be found that the interaction of science and technology with science cannot be denied. So pesantren must be prepared to deal with it. There are several Islamic boarding schools that have interacted with science and technology, both of which have greatly influenced the style of education, one of which is the Tebuireng Science Boarding School (Trensains). Santri are invited to study religion (Qur'an) as well as to study the verses of Kauniyah contained in it.Keywords: Interaction, Pesantren, Science, Technology